« Libre avec les autres » : autonomie et engagement de l’art dans la pensée d’Albert Camus - Giulio Sanseverino (Revue Italienne d'Etudes Françaises)
This article explores the relationship between aesthetics and ethics in Albert Camus’s works, emphasizing how his unique “individual balancing act” emerges from the tension between accepting reality and transcending it through creative fiction. Rather than critiquing the limitations of ideologically driven aesthetics or subordinating literature to the demands of social engagement, it highlights the productive dialectic between artistic autonomy and the external obligations of art. This distinction is framed through the contrast between the “homme révolté” (the artist) and the “révolutionnaire”, thereby shedding light on the nuanced ethical stance of Camus’s literary practice.